Correlation between transverse cerebellar diameter and gestational age in second and third trimester of singleton pregnancies - Beenish Nadeem; Anam Zahoor (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: Trans cerebellar diameter stands out as an important fetal parameter for estimating gestational age in second and third trimester when all the other parameters start showing margin of error of 3 to 4weeks. The study was designed with intent to gather more evidence on TCD measurements validity.  This will help us in using TCD on routine basis in advance pregnancies. Our objective is to determine the correlation between mean transverse cerebellar diameter and mean gestational age in 20 to 40 weeks of gestation.